Style and Flow: A Commentary on Duinker & Martin - Katz, Jonah (Empirical Musicology Review, 2017)
Duinker and Martin's excellent study presents a wealth of new data, findings, and analyses. It represents a welcome focus on the details of musical aspects of hip-hop, as well as an effort to combine those details with more global aspects of recordings in order to clarify what our notions of hip-hop 'style' or 'sound' are based on. The examination of instrumental backgrounds and production parameters is particularly novel. I would suggest, however, that the study could have benefitted from the use of details pertaining to flow, particularly in the examination of trends over time and stylistic sub-groupings. I show that several parameters pertaining to the complexity, rhythmic placement, and repetitiveness of rhymes help track changes in hip-hop style over time, distinguish between more and less similar songs, and capture effects of apparent time within the same actual time period.